ETNOMATEMATIKA PADA GERAK TARIAN DOLO-DOLO MASYARAKAT LAMAHOLOT KABUPATEN FLORES TIMUR - Fransiskus Xaverius Dalu Lewar; Natalia Peni; Finsensius Yesekiel Naja (Program Studi Pendidikan Matematika, 2022)
This study aims to find out mathematical concepts in the dolo-dolo dance movements of the Lamaholot community, East Flores Regency. This mathematical concept is used to determine the existence of mathematics in culture, especially in the culture of the East Flores area, namely in Klanelo Village. The type of research used was qualitative research and the subjects in this study were traditional elders and dolo-dolo dancers in Kawatelo Village, Demon Pagong District, East Flores Regency. In obtaining data, researchers use observation, interview, and documentation techniques. The data analysis technique uses data analysis techniques from Miles and Huberman which are divided into four stages including data collection, data reduction, data presentation, and drawing conclusions and verification. Based on the data from the research and discussion, it can be concluded that the dolo-dolo dance movement has mathematical concepts, namely: 1) Points, 2) Lines among others: Vertical Lines and Horizontal Lines, 3) Angles including: Taper Angle, Right Angle and Obtuse Angle, 4) Circle.